Nonpolar Resistive Switching of Multilayer‐hBN‐Based Memories. (14th November 2019) - Zhuang, Pingping; Lin, Weiyi; Ahn, Jaehyun; Catalano, Massimo; Chou, Harry; Roy, Anupam; Quevedo‐Lopez, Manuel; Colombo, Luigi; Cai, Weiwei; Banerjee, Sanjay K.
Abstract: Resistive switching (RS) induced by electrical bias is observed in numerous materials, including 2D hexagonal boron nitride (hBN), which has been used in resistive random access memories (RRAMs) in recent years. For practical high‐density, cross‐point memory arrays, compared with bipolar memories, nonpolar (or unipolar) devices are preferable in terms of peripheral circuit design and storage density. The non‐volatile nonpolar RS phenomenon of hBN‐based RRAMs with Ti/hBN/Au structure as a prototype is reported. Stable manual DC switching for ≈10 3 cycles with an average window over five orders of magnitude is demonstrated. After identifying a possible mechanism related to the Joule heat that contributes to the rupture of conductive filaments in nonpolar RS operations, this mechanism is validated by analyzing the occurrence of the "Re‐set" process. Though the intriguing physical origin still requires more comprehensive studies, the achievement of nonpolar RS should make it more feasible to use hBN in practical RRAM technology. Abstract : Nonpolar resistive switching (RS) is favorable for peripheral circuit design and storage density. The non‐volatile, nonpolar RS of multilayer‐hBN‐based resistive random access memories with Ti/hBN/Au structure is reported as a prototype in which stable manual direct‐current switching for ≈10 3 cycles with an average window over five orders of magnitude is demonstrated.